2022
DOI: 10.1371/journal.pone.0262372
|View full text |Cite
|
Sign up to set email alerts
|

Testing and validation of reciprocating positive displacement pump for benchtop pulsating flow model of cerebrospinal fluid production and other physiologic systems

Abstract: Background The flow of physiologic fluids through organs and organs systems is an integral component of their function. The complex fluid dynamics in many organ systems are still not completely understood, and in-vivo measurements of flow rates and pressure provide a testament to the complexity of each flow system. Variability in in-vivo measurements and the lack of control over flow characteristics leave a lot to be desired for testing and evaluation of current modes of treatments as well as future innovation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The VCTD is a gravity-driven model, which is not equivalent to how CSF flows through the body. Benchtop pump systems can simulate CSF flow with varying parameters and high precision and have been proposed as modular components of in vitro hydrocephalus models [ 14 ]. Finally, the artificially obstructed catheter was obstructed using glue, which is notably different from obstruction caused by human tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The VCTD is a gravity-driven model, which is not equivalent to how CSF flows through the body. Benchtop pump systems can simulate CSF flow with varying parameters and high precision and have been proposed as modular components of in vitro hydrocephalus models [ 14 ]. Finally, the artificially obstructed catheter was obstructed using glue, which is notably different from obstruction caused by human tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The chassis of each reciprocating positive displacement pump is comprised of 3D printed parts made of polylactic acid plastic (PLA) manufactured using an Anycubic I3 Mega printer (Anycubic Technology CO., Limited, HongKong) [ 6 ]. The design consists of five 3ml syringes per pump, allowing flow output from five total channels per pump ( Fig 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, the accuracy of the reciprocating positive displacement pump was demonstrated across a range of 0.01ml/min to 0.7ml/min with an R 2 value of 0.9998 [ 6 ]. The pump was originally produced in order to simulate the high shear rate pulsatile waveform of cerebral spinal fluid for in-vitro modelling scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…The body of each reciprocating positive displacement pump is comprised of 3D printed parts made of polylactic acid plastic (PLA) manufactured using an Anycubic I3 Mega printer (Anycubic Technology CO., Limited, HongKong) [4]. The design consists of five 3ml syringes per pump, allowing flow output from five total channels per pump (Fig 1 .).…”
Section: Reciprocating Positive Displacement Pumpmentioning
confidence: 99%